Microarray Analysis Identifies the Potential Role of Long Non-Coding RNA in Regulating Neuroinflammation during Japanese Encephalitis Virus Infection - Li, Yunchuan; Zhang, Hao; Zhu, Bibo; Ashraf, Usama; Chen, Zheng; Xu, Qiuping; Zhou, Dengyuan; Zheng, Bohan; Song, Yunfeng; Chen, Huanchun; Ye, Jing; Cao, Shengbo (Frontiers in Immunology, 2017)
Japanese encephalitis virus (JEV) is the leading cause of epidemic encephalitis worldwide. JEV-induced neuroinflammation is characterized by profound neuronal cells damage accompanied by activation of glial cells. Albeit long non-coding RNAs (lncRNAs) have been emerged as important regulatory RNAs with profound effects on various biological processes, it is unknown how lncRNAs regulate JEV-induced inflammation. Here, using microarray approach, we identified 618 lncRNAs and 1007 mRNAs differentially expressed in JEV-infected mice brain. The functional annotation analysis revealed that differentially regulated transcripts were predominantly involved in various signaling pathways related to host immune and inflammatory responses. The lncRNAs with their potential to regulate JEV-induced inflammatory response were identified by constructing the lncRNA-mRNA co-expression network. Furthermore, silencing of the two selected lncRNAs (E52329 and N54010) resulted in reducing the phosphorylation of JNK and MKK4, which are known to be involved during inflammatory response. Collectively, we first demonstrated the transcriptomic landscape of lncRNAs in mice brain infected with JEV, and analyzed the co-expression network of differentially regulated lncRNAs and mRNAs during JEV infection. Our results provide a better understanding of the host response to JEV infection, and suggest that the identified lncRNAs may be used as potential therapeutic targets for the management of Japanese encephalitis.